Metaphorical Hybridity in Knowledge Management - Roozafzai, Zahra Sadat (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study investigates metaphorical hybridity's role in shaping knowledge management practices within professional contexts. Metaphorical hybridity refers to blending diverse metaphorical representations that influence knowledge creation, organization, and dissemination within organizations. This research aims to understand how metaphorical hybridity impacts the development of novel knowledge management strategies. Q methodology was employed to analyze the metaphorical representations that shape knowledge management practices. Participants` rank-order statements related to metaphorical hybridity and knowledge management enabled the identification of common viewpoints and distinct perspectives. Key metaphorical constructs include knowledge as a fluid entity, an organic system, and a complex network. The context is the rapidly evolving knowledge landscape in professional environments, presenting challenges to effective knowledge management practices. The rise of digital technologies and globalization has further complicated knowledge management, necessitating innovative strategies. Findings demonstrate metaphorical hybridity's dynamic nature and its potential to foster adaptability, innovation, and resilience in knowledge management practices. The research highlights the importance of understanding the interplay between diverse perspectives, representations, and knowledge management approaches. Implications include recognizing metaphorical hybridity's influence for harnessing diverse metaphors' power more effectively and the practical adaptability to the changing knowledge landscape and address complex challenges associated with managing knowledge in contemporary professional environments.